STUDIES ON FOLIAR FEEDING EFFECT OF NUTRIENTS ON QUALITY AND YIELD OF GUAVA (PSIDIUM GUAJAVA L.) CV. SHWETA - EKTA SINGH; BHAGWAN DEEN (The Bioscan, 2025)
The present investigation entitled “Studies on Foliar Feeding Effect of Nutrients on Quality and Yield of Guava (Psidium guajava L.) cv. Shweta” was carried out during the year 2024-2025 at Main Experiment Station, Department of Fruit Science, College of Horticulture and Forestry, ANDUAT, Kumarganj, Ayodhya, Uttar Pradesh, India.